Entrepreneurship: The Act of Enhancing One's Reality - Andruin Mui (European Regional Science Association (ERSA), 2010)
In the research field of entrepreneurship there has not yet been a consensus on the most appropriate definition and conceptual framework of entrepreneurship. This paper aims to fill this persistent gap in entrepreneurship research. The conceptual framework and definition proposed in this paper, "The Act of Enhancing One's Reality", unifies the trait approach and the behavioural approach used by entrepreneurship scholars. It forges a link between entrepreneurship research and other social sciences, rendering Maslow's hierarchy of needs empirically testable. It sheds light on how opportunities come into existence as well as how they are recognized. It provides insight into the relation between micro-level entrepreneurial action and macro-level economic growth. And finally, it creates the unique interdisciplinary domain of reality enhancement for the research field of entrepreneurship. The new definition and conceptual framework proposed in this paper is consistent with the critique, insights and results yielded from past research on entrepreneurship and it shows promise that it is indeed possible to foster the successful and innovative kind of entrepreneurship that promotes economic growth. Moreover, it is able to provide consistent explanations to questions past entrepreneurship research had sought to answer. But most importantly, the proposed definition and conceptual framework of entrepreneurship is universal in its applicability for scholars from a wide variety of disciplines, for policymakers of advanced economies as well as policymakers of developing economies. Entrepreneurship is not only limited to the realm of economics nor limited to the start up of firms and profit making. Entrepreneurship, as defined in this paper, is the very essence of humankind. From the first handmade fires to the nuclear power plants of today, from Icarus' wings to men on the moon, the progress we have made as humankind and our very existence as we know it today is the result of the ever continuing accumulation of entrepreneurial action. The proposed definition and conceptual framework of entrepreneurship offers insight into the progress we have made in the past, the progress we can make now and the progress we as one people are still able to make in the future.
Keywords: 330